EFEKTIVITAS TERAPI MUSIK SEBAGAI PENDEKATAN NON-FARMAKOLOGIS PADA PASIEN DENGAN GANGGUAN KECEMASAN - Yurnalis, Yurnalis; Mutiara Anissa (Yayasan Nusantara Hasana Berdikari, 2025)
Anxiety disorders are one of the most common mental health problems that have a significant impact on an individual's quality of life and productivity. In addition to pharmacological therapy and psychotherapy, music therapy is beginning to be widely used as a non-pharmacological approach to reduce anxiety and improve emotional well-being. This study aimed to evaluate the effectiveness of music therapy as a mental health support intervention in patients with anxiety disorders through a systematic literature review. This study used a systematic literature review method with meta-synthesis, analyzing 21 qualitative and quantitative studies selected from PubMed, EBSCO, and Google Scholar databases (period 2015–2024). Inclusion criteria include studies with a population of patients with anxiety disorders, music therapy interventions, as well as reports of anxiety or quality of life outcomes. Of the 1,463 articles screened, 21 studies were included in the analysis. Results showed that music therapy, both actively (playing or singing) and receptive (listening), was consistently effective in lowering anxiety levels, improving sleep quality, mood, and improving social function in various population groups, including medical patients, college students, and the elderly. Meta-analyses showed high effectiveness of music therapy (effect size Hedges' g >1), with additional benefits in the form of increased motivation and emotional regulation. The combination of music therapy with other interventions such as pharmacotherapy, CBT, or mindfulness improves clinical outcomes. Music therapy is an effective, safe, easy, and affordable non-pharmacological approach to overcome anxiety disorders and improve mental health. The integration of music therapy in mental health services deserves to be considered as part of a comprehensive approach. Further research is needed for protocol optimization and exploration of neurophysiological mechanisms of music therapy in various populations.